The RanBP2/RanGAP1*SUMO1/Ubc9 SUMO E3 ligase is a disassembly machine for Crm1-dependent nuclear export complexes - Ritterhoff, Tobias; Das, Hrishikesh; Hofhaus, Götz; Schröder, Rasmus R.; Flotho, Annette; Melchior, Frauke (Nature Communications, 2016)
Continuous cycles of nucleo-cytoplasmic transport require disassembly of transport receptor-Ran-GTP complexes in the cytoplasm. Here the authors elucidate the specific function of the RanBP2 complex in the disassembly process.